2011
DOI: 10.1038/modpathol.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

MAGEC2 is a sensitive and novel marker for seminoma: a tissue microarray analysis of 325 testicular germ cell tumors

Abstract: Melanoma-associated gene C2 (MAGEC2) is a recently identified cancer testis antigen expressed in normal testicular and placental tissue. It has been detected in some human carcinomas, but its expression in primary testicular germ cell tumors is unknown. Immunohistochemistry was used to study MAGEC2 protein in 325 primary testicular germ cell tumors, including 94 mixed germ cell tumors. Seminomatous and nonseminomatous components were separately arranged and evaluated on tissue microarrays. MAGEC2 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…Expression of KIT depends on the antibody used. 27,45 Rajpert-De Meyts et al 35 already demonstrated that spermatocytic seminoma expresses the cancer testis antigen MAGEA4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of KIT depends on the antibody used. 27,45 Rajpert-De Meyts et al 35 already demonstrated that spermatocytic seminoma expresses the cancer testis antigen MAGEA4.…”
Section: Discussionmentioning
confidence: 99%
“…27 In summary, the tissue microarray contained testicular tumor components of 254 seminomas, 89 embryonal carcinomas, 51 yolk sac tumors, 54 teratomas, 10 choriocarcinomas and 4 spermatocytic seminomas. Additionally, we included intratubular germ cell neoplasia unclassified and non-tumor testicular tissue from 20 tumor patients.…”
Section: Tissue Microarraymentioning
confidence: 99%
“…This newer allows a reliable distinction of seminoma from embryonal carcinomas. Therefore, MAGEC2 represents an additional tool for the differential diagnosis of testicular germ cell tumours (Bode et al, 2011).…”
Section: Genetic Markersmentioning
confidence: 99%
“…Although the morphological features of seminoma are similar irrespective of primary tumor site, differences have been described between the expression of immunohistochemical markers and genetic profiles of testicular and mediastinal seminomas (5)(6)(7)(8). Several more recent publications have investigated the expression pattern of various novel immunohistochemical markers -including stem cell markers -in testicular seminomas (9)(10)(11)(12)(13)(14)(15)(16) …”
Section: Introductionmentioning
confidence: 97%
“…Expression of OCT3/4 has been shown to be useful diagnostic tool in the identification of the more undifferentiated germ cell tumors of the testis, ie. seminoma and embryonal carcinoma(9)(10)(11) 28). This marker has not only been proven valuable for the diagnosis of testicular seminomas but also for establishing germ cell origin in metastatic disease (29, 30).…”
mentioning
confidence: 99%